Development of Allele-Specific Therapeutic siRNA in Meesmann Epithelial Corneal Dystrophy. - IRVINE, ALAN (My University, 2011)
BACKGROUND: Meesmann epithelial corneal dystrophy (MECD) is an inherited eye disorder caused by dominant-negative mutations in either keratins K3 or K12, leading to mechanical fragility of the anterior corneal epithelium, the outermost covering of the eye. Typically, patients suffer from lifelong irritation of the eye and/or photophobia but rarely lose visual acuity; however, some individuals are severely affected, with corneal scarring requiring transplant surgery. At present no treatment exists which addresses the underlying pathology of corneal dystrophy. The aim of this study was to design and assess the efficacy and potency of an allele-specific siRNA approach as a future treatment for MECD. METHODS AND FINDINGS: We studied a family with a consistently severe phenotype where all affected persons were shown to carry heterozygous missense mutation Leu132Pro in the KRT12 gene. Using a cell-culture assay of keratin filament formation, mutation Leu132Pro was shown to be significantly more disruptive than the most common mutation, Arg135Thr, which is associated with typical, mild MECD. A siRNA sequence walk identified a number of potent inhibitors for the mutant allele, which had no appreciable effect on wild-type K12. The most specific and potent inhibitors were shown to completely block mutant K12 protein expression with negligible effect on wild-type K12 or other closely related keratins. Cells transfected with wild-type K12-EGFP construct show a predominantly normal keratin filament formation with only 5% aggregate formation, while transfection with mutant K12-EGFP construct resulted in a significantly higher percentage of keratin aggregates (41.75%; p<0.001 with 95% confidence limits). The lead siRNA inhibitor significantly rescued the ability to form keratin filaments (74.75% of the cells contained normal keratin filaments; p<0.001 with 95% confidence limits). CONCLUSIONS: This study demonstrates that it is feasible to design highly potent siRNA against mutant alleles with single-nucleotide specificity for future treatment of MECD.
PUBLISHED
Keywords: Ophthalmology; MECD; Immunology, Inflammation & Infection